Enhanced Social Accountability Through Open Access to Data : Geomapping World Bank Projects - Gigler, Björn-Sören (2012)
The 2004 World Development Report, Making Services Work for Poor People, argues that the welfare of the world’s most vulnerable people depends directly on the availability of public services. Opening access to data is an important step toward improving the performance of public institutions in providing public services, and more broadly, to enhance support for good governance and social accountability.